Evaluation of sand-geomembrane interface behavior using discrete element method - Ari, Abdulmuttalip; Akbulut, Suat (SPRINGER, 2022)
In this study, the shear behavior of the sand-geomembrane interface was investigated in micro-scale using discrete element method. For this purpose, interface direct shear tests were simulated using the discrete element method for three sands with different shapes and three geomembranes with various roughness. In the simulations, realistic particle shape and surface roughness were adopted using image processing techniques. The shear strain-stress relationships of the laboratory interface tests were employed to calibrate the friction coefficient of simulated interfaces. The evolution of particle response was monitored throughout the shearing process for displacement, porosity, particle contact, and anisotropy mechanisms. It was observed that the micro-scale responses of interfaces have varied with the particle shape and surface roughness parameters. As a result, the reason for the variations in interface shear strength was produced by examining the evolution of particle state in microscale.
Keywords: Interface shear; Sand; Geomembrane; Microscale; Discrete element modeling; SHEAR-STRENGTH; PARTICLE-SHAPE; SIMULATIONS; Materials Science; Mechanics; Physics